2021
DOI: 10.3390/jcm10081610
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and White Blood Cell Count in Non-Infective Acute Ischemic Stroke Patients Treated with Intravenous Thrombolysis

Abstract: Background: Previous studies on inflammatory biomarkers in acute ischemic stroke (AIS) produced divergent results. We evaluated whether C-reactive protein (CRP) and white blood cell count (WBC) measured fasting 12–24 h after intravenous thrombolysis (IVT) were associated with outcome in AIS patients without concomitant infection. Methods: The study included 352 AIS patients treated with IVT. Excluded were patients with community-acquired or nosocomial infection. Outcome was measured on discharge and 90 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As shown in our previous study, CRP levels evaluated in a different time window, i.e. 12-24 hours after IVT, were an independent risk factor for poor short-term and long-term outcomes and were also associated with in-hospital mortality [20]. Analysis of healthy individuals showed that people aged 65 or more had significantly higher CRP levels than their younger counterparts [21].…”
Section: Discussionmentioning
confidence: 51%
“…As shown in our previous study, CRP levels evaluated in a different time window, i.e. 12-24 hours after IVT, were an independent risk factor for poor short-term and long-term outcomes and were also associated with in-hospital mortality [20]. Analysis of healthy individuals showed that people aged 65 or more had significantly higher CRP levels than their younger counterparts [21].…”
Section: Discussionmentioning
confidence: 51%
“… 13 Non-infective C-reactive protein level is an independent risk factor for poor prognosis in AIS patients with IVT treatment. 14 Besides, previous literatures also suggested that increased plasma fibrinogen was associated with reduced chance of favorable outcome in ischemic stroke patients. 15 , 16 Consistent with the previous data, our study demonstrated that AIS patients with poor outcome tended to have lower globulin levels.…”
Section: Discussionmentioning
confidence: 98%
“…However, the evaluation of a single-cellular type is insufficient for an estimation of the status of the immune response. Moreover, certain external disruptive factors may affect the blood routine examination, 40 and therefore, a variety of ratios or indices that incorporate multiple cell detection values are generally applied in clinical practice 14–16 . These measurements have been demonstrated to be more reliable than assessments based on a single-cellular type 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the association between the clinical outcome and inflammatory biomarkers in the serum of patients with AIS; 10–13 however, the association between inflammatory biomarkers in the serum and functional recovery in AIS patients who undergo IVT is limited. To the best of our knowledge, various inflammatory indexes, including the lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR), high-sensitivity C-reactive protein, and platelet-to-lymphocyte ratio (PLR), are involved in the outcome of patients with AIS 14–16 . Nevertheless, the mechanisms potentially associated with inflammatory responses in the pathology of AIS have yet to be fully elucidated; moreover, the relationship between the outcomes of AIS and the inflammatory factors merits further determination.…”
mentioning
confidence: 99%